Mediated moderation of organisational and government support on workplace adaptation of Malaysian professional returnees - Kunasegaran, Mageswari (2016)
This study investigates the relationship between talent development environment (TDE) constructs and the workplace adaptation (WA) of Malaysian professional returnees as mediates by organisational support and moderate by the government support. Workplace adaptation refers to process of adapting and adjusting process in the new working environment. Professional returnees are defined as a group of individual who have left the country to further their study or work abroad and returned to Malaysia. This study aims to identify the returnees’ characteristics, returnees’ job location, the influences of mediator and moderator on WA. This study adapted the TDE model, which was frequently used in the sports science management into HRD context. There were eight independent constructs, one mediator and one moderator were used to analyse WA of the returnees. This study further adopted the Work Adjustment Theory, Person-Environment fit Theory, Organisational Support Theory and Social Exchange Theory in explaining WA. There were 157 respondents participated in this study who were selected using snowball sampling technique. The data were analysed using the Partial Least Square-Structural Equation Modelling version 3 (PLS-SEM) in a reflective-formative assessment structure. The results demonstrate mixed outcomes in the direct, indirect and moderation interaction effect. There was only one hypothesis relationship was supported, meanwhile through mediation effect, there was two hypothesis relationship were accepted. The organisational support has a strong mediation effect. Similarly, the government support also has a significant value but negative correlation in the WA study. The findings indicate that the job focus and long-term development were important constructs in WA study. This study reveals the importance of organisational support as mediator to help returnees to adapt in their WA.